A study on the relationship between social networking sites (SNSs) and employees' productivity in Institut Aminuddin Baki Cawangan Genting Highlands based on employees' perceptions / Nur Farhana Mazlan - Mazlan, Nur Farhana (2016)
The purpose of this study was to identify the relationship between Social Networking Sites (SNSs) and employees' productivity in Institut Aminuddin Baki Cawangan Genting Highlands based on employees' perceptions. The two factors that influence the use of SNSs at workplace were personal use and organizational use. It was measured by level of employees' productivity such as low, medium and high. The researcher used descriptive and correlational research for research design. Sampling frame were taken from list of employees in Institut Aminuddin Baki Cawangan Genting Highlands. The respondents for this study were 36 management staff in Institut Aminuddin Baki Cawangan Genting Highlands from Unit Pentadbiran & Perkhidmatan, Unit Kewangan, Unit Pengurusan Lalihall and Others Unit. The sampling method utilized as a part of this study was simple random sampling. The researcher develop and distributed the questionnaire personally by hand to the respondents. In order to perform the statistical analysis, Statistical Packages for the Social Science (SPSS) version 20.0 was used. The findings conclude that there is a positive and strong relationship between SNSs employees' productivity based on the employees' perceptions.